We Learn More Than Just Writing - Kami Day (Journal of the Assembly for Expanded Perspectives on Learning, 2005)
In a composition class, students learn a great deal more, for good or ill, than just strategies for writing. This article shows that, as students and teachers learn to recognize and value their own inner teachers, they can also develop relationships with each other that nourish their spirits as well as their intellects.